2017
DOI: 10.3892/ol.2017.7176
|View full text |Cite
|
Sign up to set email alerts
|

Metformin in combination with cisplatin inhibits cell viability and induces apoptosis of human ovarian cancer cells by inactivating ERK 1/2

Abstract: Abstract. Metformin protects against insulin resistance by restoring insulin sensitivity and may also possess anticancer activity. The aim of the present study was to investigate the effects of metformin alone or combined with cisplatin (DDP) on the cell viability and apoptosis of HO-8910 human ovarian cancer cells, and to investigate metformin as a potential novel therapeutic for treating ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
4
23
0
Order By: Relevance
“…Our results are in agreement with a study showing enhanced chemosensitivity of ovarian cancer cisplatin-resistant cells following treatment with BEZ235, which was accompanied by marked attenuation of PI3K/AKT pathway [46]. A recent study suggested that metformin combined with cisplatin impeded cell viability and caused apoptosis by inactivating ERK 1/2 in human ovarian cancer cells [49].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with a study showing enhanced chemosensitivity of ovarian cancer cisplatin-resistant cells following treatment with BEZ235, which was accompanied by marked attenuation of PI3K/AKT pathway [46]. A recent study suggested that metformin combined with cisplatin impeded cell viability and caused apoptosis by inactivating ERK 1/2 in human ovarian cancer cells [49].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, several studies have suggested that inhibition of the MEK/ERK pathway disrupts functions essential for ovarian cancer progression (29,35,37). Dang et al (39) reported that metformin in combination with cisplatin inhibits cell viability and induces apoptosis of human ovarian cancer cells by inactivating ERK. In another study, Chan et al (40) demonstrated that therapies targeting the ERK signaling pathway reduce the aggressiveness of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…45,49,50 Interestingly, recent studies show that metformin, usually applied in diabetic patients, prevents tumor growth, induces apoptosis and increases sensitivity to chemotherapy in ovarian cancer cells. [51][52][53][54][55][56][57] Mechanisms underlying these cellular effects include suppression of cancer stem cells, inhibition of epithelial-to-mesenchymal transition and interference with neoplastic cell metabolism. [58][59][60][61][62] Following promising data of epidemiological studies showing a favorable effect of metformin on ovarian cancer Figure 6 Summary of the hypothesized interaction within the NRF2/AKR1C1/PR pathway.…”
Section: Discussionmentioning
confidence: 99%